2016
DOI: 10.3347/kjp.2016.54.4.537
|View full text |Cite
|
Sign up to set email alerts
|

Stellantchasmus falcatus (Digenea: Heterophyidae) in Cambodia: Discovery of Metacercariae in Mullets and Recovery of Adult Flukes in an Experimental Hamster

Abstract: Stellantchasmus falcatus (Digenea: Heterophyidae) is first reported from Cambodia through recovery of the metacercariae from mullet fish and adult flukes from an experimentally infected hamster. We purchased 7 mullets, Chelon macrolepis, in a local market of Phnom Penh, Cambodia, and each of them was examined by the artificial digestion method on May 2010. The metacercariae of S. falcatus were detected in all mullets (100%) examined, and their average density was 177 per fish. They were elliptical, 220×168 μm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…In addition, S. falcatus metacercariae were similar in size to S. fal-catus metacercariae (220 × 168 µm in average size) in mullet from Cambodia. Their prevalence and average intensity were 100% and 177 metacercariae per fish infected, respectively [17]. In contrast, they were somewhat smaller than those from the mullet in Vietnam.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In addition, S. falcatus metacercariae were similar in size to S. fal-catus metacercariae (220 × 168 µm in average size) in mullet from Cambodia. Their prevalence and average intensity were 100% and 177 metacercariae per fish infected, respectively [17]. In contrast, they were somewhat smaller than those from the mullet in Vietnam.…”
Section: Discussionmentioning
confidence: 87%
“…The metacercariae were 297× 232 µm in size and had a V-shaped excretory bladder [18]. Many species of fish, including the wrestling halfbeak, garfish (Xenentodon canciloides), mullet (Mugil cephalus), mullet (C. macrolepis), common carp (Cyprinus carpio), and grass carp (Ctenopharyngodon idella) have been reported to be the second intermediate hosts for S. falcatus metacercariae in Thailand, Myanmar, Laos, Cambodia, Korea, and Vietnam [10,17,19,20]. Recently, Wongsawad et al [7] reported that the metacercariae found in the wrestling halfbeak in Chiang Mai province was S. dermogenysi n.…”
Section: Discussionmentioning
confidence: 99%
“…The metacercariae of S. falcatus were detected only in the mullet, Chelon macrolepis , like in Cambodia [ 37 ]. They were also found in several species of fish, i.e., mullet ( M. cephalus and L. haematocheila ), goby ( A. flavimanus ), wrestling halfbeak ( D. pusilla ), X. canciloides , giant gouramy ( O. gourami ), common carp ( C. carpio ), and grass carp ( C. idella ), in Japan, Hawaii, China, Korea, Thailand, Vietnam, and Lao PDR [ 38 – 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…They were also found in several species of fish, i.e., mullet ( M. cephalus and L. haematocheila ), goby ( A. flavimanus ), wrestling halfbeak ( D. pusilla ), X. canciloides , giant gouramy ( O. gourami ), common carp ( C. carpio ), and grass carp ( C. idella ), in Japan, Hawaii, China, Korea, Thailand, Vietnam, and Lao PDR [ 38 – 45 ]. Among these fish intermediate hosts, the mullet is the most frequently reported in various regions [ 25 , 37 41 ]. The size of S. falcatus metacercariae in this study (225×165) were nearly the same with those in Cambodia (220×168), but somewhat smaller than those in Vietnam (297×232) [ 25 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation